Flood Modeling of Jatiroto River Using HEC-RAS to Determine Effective Flood Control Alternatives - Sumiadi Sumiadi; Bambang Winarta; Dwi Priyantoro; Mohammad Taufiq; Rovita Yuniarti Arimbi (Kadiri University, 2022)
Jatiroto River, located on the border of Lumajang and Jember Regencies, is one of the rivers with a risk of flooding. This is due to changes in land use and high sedimentation. For this reason, flood control efforts are needed to reduce disaster risk. This study aims to conduct flood modeling on the Jatiroto River and propose the most effective flood control. In this paper, the flood modeling uses HEC-RAS 5.0 with Q25y and Q50y obtained from analyzing rainfall data from 9 rainfall stations. The first modeling was carried out to produce a flow hydrograph on the upstream river section. The second modeling is carried out for the downstream river section with lateral flow from the Jatiroto tributaries. The flood modeling results show that the existing cross-sectional capacity of the Jatiroto River cannot accommodate Q25y, so it overflows in several cross-sections, especially the downstream section.By normalizing the river's cross-section and constructing an embankment in the downstream area, the flow simulation results on flood modeling show that the flood discharge at 25 years and 50 years does not overflow in all cross sections. Therefore, the normalization and construction of embankments become the effective flood control option in the Jatiroto River.